The Right To Self-Determination Of Peoples, Referendum Experiences As A Model - Sleman Abdullah Ismael; Sasan Hikmat Ali (QALAAI ZANIST JOURNAL, 2023)
The right of peoples to self-determination was considered one of the basic rights agreed upon by the international community during the emergence of liberation movements and revolutions calling for independence, and consequently it became the legal basis on which to focus on countries and peoples that justify their legitimate struggle and resistance against the forces of colonialism and occupation. Because of the developments and events that the world witnessed and the results that led to it, the right to self-determination has a meaning contrary to what it originally came with, which is to get rid of colonial control, which is the right to secede from the mother state by justifying giving minorities in the state the right to secede. And the formation of a state for them. One of the peaceful methods that people resort to in determining their destiny is direct referendum, as we address it in our study by presenting the experiences of states in independence through a referendum. . For this, the work is containing firstly, an introduction; Secondly, concepts and principles of self-determination; Thirdly, Self-determination based on principles, constitutions, and international agreements; and finally, referendum and its consequences under the light of international experiments. At the end of this work, results and recommendations will be shown.